Pendidikan Karakter Dan Disiplin Dalam Esktrakurikuler Berkuda Di Pondok Pesantren PKP Al-Hidayah - Setia Wati; Rhesti Laila Ulfa (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
Character education and discipline are important elements in shaping the superior personality of students, especially in the pesantren environment. This study aims to describe the implementation of character and discipline education through equestrian extracurricular activities at Pondok Pesantren PKP Al-Hidayah. The approach used is qualitative with a descriptive method, involving observation, interviews, and documentation as data collection techniques. The research results show that horseback riding extracurricular activities not only serve as a means of developing riding skills but also instill character values such as responsibility, honesty, cooperation, and courage. In addition, this activity trains discipline through strict rules related to training schedules, horse care, and adherence to instructors. The implementation of character education and discipline in horseback riding activities is supported by continuous coaching and a conducive pesantren environment. This research concludes that horseback riding extracurricular activities significantly contribute to shaping the character and discipline of students, making it an innovative character education model in Islamic boarding schools. Keywords: character education, discipline, equestrian extracurricular activities, pesantren